2019
DOI: 10.6007/ijarped/v8-i4/6817
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review on Secondary School Students’ Mathematics Self-Efficacy

Abstract: Mathematics self-efficacy is one of the essential behavioural factors in mathematics learning for students. The aim of this review was to determine the relationship of secondary school students' mathematics self-efficacy and their performance in mathematics. Other than that, this review also studied the factors that can influence secondary school students' mathematics self-efficacy. The articles were collected from January 2015 until 2019 across one of the Google Scholar databases. A total of 26 studies were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Mathematics self-efficacy (MSE) is one of the crucial factors in students' mathematics learning (Roslan and Maat, 2019). It is a stronger predictor of math performance than math anxiety (Pajares and Miller, 1994), previous math experience (Pajares and Kranzler, 1995b), mathematics self-concept, perceived usefulness of mathematics, prior experience with mathematics, or gender (Pajares and Miller, 1994) and influences math performance as strongly as overall mental ability (Pajares and Kranzler, 1995a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematics self-efficacy (MSE) is one of the crucial factors in students' mathematics learning (Roslan and Maat, 2019). It is a stronger predictor of math performance than math anxiety (Pajares and Miller, 1994), previous math experience (Pajares and Kranzler, 1995b), mathematics self-concept, perceived usefulness of mathematics, prior experience with mathematics, or gender (Pajares and Miller, 1994) and influences math performance as strongly as overall mental ability (Pajares and Kranzler, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of studies, it was found that MSE is an important predictor of high school students' mathematics achievement (Roslan and Maat, 2019). In two studies in Greece among students from grades 7-11 mathematics self-efficacy significantly predicted mathematics achievement using data from the Program for International Student Assessment (PISA) (Cheema, 2018;Hiller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Following this, researchers are investigating using different theoretical and empirical frameworks that can give direction for the way determinants of students' mathematics achievement could be identified (Zakariya, 2022). The theoretical frameworks used in this article focused more on discussions of social cognitive theory by Bandura (Roslan & Maat, 2019; Schöber et al, 2018), self‐efficacy theory by Bandura, and Schunk (Silver et al, 2001), and others related to the study under investigation. Most of the studies used in this article observed the students' mathematics self‐efficacy theory based on the students' mathematics perception and self‐efficacy combining them with mathematics achievement (Appiah et al, 2022; Sakellariou, 2022; Yesuf et al, 2023).…”
Section: Introductionmentioning
confidence: 99%